1992
DOI: 10.1002/food.19920360611
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic dephosphorylation of caseins and creaming behaviour of o/w emulsions stabilized with dephosphorylated casein fractions

Abstract: Summaryas-and 8-casein were treated with acid or alkaline phosphatase. The dependence of the dephosphorylation on incubation time was investigated by electrophoresis and by determination of the residual phosphate content. The degree of dephosphorylation is correlated with the stability of emulsions prepared with the modified proteins. Incubation of as-and p-casein with alkaline phosphatase increased the creaming stability 6-and 10-fold respectively. Zusammenfassung Enzymatische Dephosphorylierung von Caseinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The micro-structure of acid curds made with native and dephosphorylated casein micelles showed also major differences (Li-Chan and Nakai 1989). Lorenzen and Reimerdes (1992) showed that dephosphorylation of α s -and β-casein stabilized the creaming behavior of oil/water emulsions. By molecular dynamics, Cassiano and Area (2003) reported that the affinity of totally dephosphorylated β-casein for water/lipid interface was lower than β-casein which was able to be inserted in the water/lipid interface.…”
Section: Dephosphorylationmentioning
confidence: 99%
“…The micro-structure of acid curds made with native and dephosphorylated casein micelles showed also major differences (Li-Chan and Nakai 1989). Lorenzen and Reimerdes (1992) showed that dephosphorylation of α s -and β-casein stabilized the creaming behavior of oil/water emulsions. By molecular dynamics, Cassiano and Area (2003) reported that the affinity of totally dephosphorylated β-casein for water/lipid interface was lower than β-casein which was able to be inserted in the water/lipid interface.…”
Section: Dephosphorylationmentioning
confidence: 99%
“…The release of phosphate groups resulted in lower calcium sensitivity and softer curd during cheese making. LORENZEN and REIMERDES (1992) reported that the modification with alkaline and acid phosphatases increased the emulsion stability. In contrast, HUSBAND and coworkers (1997) showed a decrease in emulsion stability and an increase in foamability for dephosphorylated β-cn (dp-β-cn).…”
mentioning
confidence: 99%
“…In addition, less stable emulsions were also formed from dephosphorylated casein than from unmodified casein (Van Hekken and Strange, 1993). However, emulsions formed from isolated a s -casein or b-casein were shown to be considerably more stable to creaming than their control counterparts (Lorenzen and Reimerdes, 1992). More recently, McCarthy et al (2013) showed that partially dephosphorylated b-casein resulted in less efficient emulsification than the untreated protein, but the globules coated in the modified protein were more stable against calcium-induced aggregation, whereas the dephosphorylated protein failed to form a gel, unlike the control protein.…”
Section: Enzymatic Dephosphorylation Of Milk Proteinsmentioning
confidence: 97%